2018
DOI: 10.1590/1414-431x20176891
|View full text |Cite
|
Sign up to set email alerts
|

Tea polyphenols induce S phase arrest and apoptosis in gallbladder cancer cells

Abstract: Gallbladder cancer (GBC) is the most common malignancy in the biliary tract. Without effective treatment, its prognosis is notoriously poor. Tea polyphenols (TPs) have many pharmacological and health benefits, including antioxidant, anti-inflammatory, anti-tumor, anti-thrombotic, antibacterial, and vasodilatory properties. However, the anti-cancer effect of TPs in human gallbladder cancer has not yet been determined. Cell viability and colony formation assay were used to investigate the cell growth. Cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…EGCG and theaflavins induce apoptosis in human cervical cancer cells by suppressing the activation of NF-jB and Akt via blocking phosphorylation of jBa and jBb subunits, thus down-regulating COX-2 (Singh et al 2011). Other molecular mechanisms of apoptosis induction by tea polyphenols include upregulating the expression levels of p53, p21, p73, caspase-3, caspase-9, caspase-8, and Bax; while down-regulating the expression levels of Bcl-2 and Bcl-xL (Zhao et al 2014;Wang et al 2018). Synergistic anticancer effects of bleomycin and tea polyphenols in human cervical cancer cells via induction of apoptotic pathways were studied, and it was suggested that both of these agents might provide an effective combination therapy for cervical cancer (Alshatwi et al 2016).…”
Section: Effect On Apoptosismentioning
confidence: 99%
“…EGCG and theaflavins induce apoptosis in human cervical cancer cells by suppressing the activation of NF-jB and Akt via blocking phosphorylation of jBa and jBb subunits, thus down-regulating COX-2 (Singh et al 2011). Other molecular mechanisms of apoptosis induction by tea polyphenols include upregulating the expression levels of p53, p21, p73, caspase-3, caspase-9, caspase-8, and Bax; while down-regulating the expression levels of Bcl-2 and Bcl-xL (Zhao et al 2014;Wang et al 2018). Synergistic anticancer effects of bleomycin and tea polyphenols in human cervical cancer cells via induction of apoptotic pathways were studied, and it was suggested that both of these agents might provide an effective combination therapy for cervical cancer (Alshatwi et al 2016).…”
Section: Effect On Apoptosismentioning
confidence: 99%
“…Various cancer-related molecules have been reported to be modulated by GTPs. In fact, many studies have reported that GTPs inhibited cell growth and induced apoptosis in various types of malignancies [ 19 , 27 , 28 ]. In addition, these polyphenols modulate the functions of various cancer-related signaling molecules.…”
Section: Anticancer Effects Of Green Tea Polyphenolsmentioning
confidence: 99%
“…In general, GTPs are considered to be safe because they are natural compounds. GTPs were found to have no toxic effects on normal cells in the gallbladder [ 28 ]. Furthermore, 24-h treatment with 20 μg/mL and 40 μg/mL of EGCG increased the frequency of apoptotic cells in colon cancer cell lines (COLO205), while no significant changes were observed in normal colon epithelial cells (NCM460) [ 19 ].…”
Section: Bladder Cancer and Green Teamentioning
confidence: 99%
“…Many interesting findings have also been published regarding the protective benefits of polyphenols against cancer. Studies have shown how treatment with 140 µM tea polyphenols induces mitochondrial-mediated apoptosis by activating the caspase-3 and PARP apoptotic cascade in human gallbladder cancer cells [53], 0.5-5 µg/mL of EGCG reduces the cell viability and increases the apoptosis rate of myeloid-derived suppressor cells, mainly through the Arg-1/iNOS/Nox2/NF-κB/STAT3 signaling pathway [54], and 15 µM EGCG inhibits Excision Repair Cross-Complementation Group1/Xeroderma Pigmentosum group F, thereby inhibiting DNA repair and enhancing cisplatin sensitivity in human lung cancer cells [55]. A total of 0.1-1 mM catechin with lysine has also been proven to have antimigratory effects in breast, pancreatic, and colorectal cell lines through JAK2/STAT3 and Wnt pathway inhibition [56].…”
Section: Cancermentioning
confidence: 99%